ANALYSIS ON LEXICAL DENSITY AND SOPHISTICATION IN KOREAN LEARNERS’ SPOKEN LANGUAGE - Lee, Bomi (PEOPLE: International Journal of Social Sciences, 2019)
The proficiency level of second language development can be judged by the learner’s output and be used to estimate the learner’s stage of learning. The linguistic production can be used to see how a learner’s language knowledge has been internalized. In this case, factors such as accuracy, fluency, and complexity can be considered. In this study, lexical density and sophistication were analyzed in Korean learners’ spoken production as an aspect of measuring lexical complexity. The lexical density and sophistication scores were obtained from 44 students’ spoken data whose language proficiency varied from intermediate (level 3 and 4) to advanced (level 5 and 6). Also, using one-way ANOVA, statistical analysis was conducted on the differences according to the proficiency of each level. As a result, the lexical density score showed little difference according to the proficiency level, however the difference was statistically not significant. However, in the case of lexical sophistication score, the scores of advanced students were higher the intermediate students. The level of lexical sophistication corresponded with the proficiency level increased, and the differences were statistically significant.